2013
DOI: 10.1002/emmm.201202168
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of cardiomyopathy through U7snRNA‐mediated exon skipping in Mybpc3‐targeted knock‐in mice

Abstract: Exon skipping mediated by antisense oligoribonucleotides (AON) is a promising therapeutic approach for genetic disorders, but has not yet been evaluated for cardiac diseases. We investigated the feasibility and efficacy of viral-mediated AON transfer in a Mybpc3-targeted knock-in (KI) mouse model of hypertrophic cardiomyopathy (HCM). KI mice carry a homozygous G>A transition in exon 6, which results in three different aberrant mRNAs. We identified an alternative variant (Var-4) deleted of exons 5–6 in wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
82
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 64 publications
1
82
0
Order By: Relevance
“…Classical treatments of HCM target symptoms and LV outflow tract obstruction with pharmacological and/or surgical treatments, but do not address the cause of the disease 29,30 . New strategies targeting the endogenous mutant pre-mRNA or RNA such as exon skipping, exon inclusion, trans-splicing and ARTICLE RNA silencing, opened the perspective for a causal therapy for patients with HCM 2,21,22,31,32 . These proof-of-concept studies still have major limitations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Classical treatments of HCM target symptoms and LV outflow tract obstruction with pharmacological and/or surgical treatments, but do not address the cause of the disease 29,30 . New strategies targeting the endogenous mutant pre-mRNA or RNA such as exon skipping, exon inclusion, trans-splicing and ARTICLE RNA silencing, opened the perspective for a causal therapy for patients with HCM 2,21,22,31,32 . These proof-of-concept studies still have major limitations.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that a 5 0 -transsplicing approach corrects the mutation in cardiac myocytes and in vivo in HCM KI mice, but its efficiency was too low to prevent or rescue the disease phenotype 22 . In-frame skipping of mutated exons by antisense oligonucleotides inserted in U7snRNA produced a stable functional protein and transiently rescued the cardiac phenotype in KI mice 21 . In both cases, however, the amount of repaired protein remained very low 21,22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations